Poroelasticity of carbonates with fractured grains and fluid‐saturated pores. (18th October 2014) - Berryman, James G.; de Borst, R.; Borja, R. I.; Darve, F.; Pijaudier‐Cabot, G.; Whittle, A. J.
Summary Geomechanical analysis needed to treat anisotropic (specifically trigonal symmetry) grains of carbonates jumbled together to form an overall isotropic polycrystalline poroelastic material is summarized. Poroelastic effects enter the problem via fractured anisotropic solids saturated by fluids. Copyright © 2014 John Wiley & Sons, Ltd.